Study of growth fraction on fine needle aspirated prostatic tissue smear using monoclonal antibody Ki-67 - Sai, S (Hinyokika kiyo. Acta urologica Japonica, 1991)
Immunohistochemical staining using monoclonal antibody Ki-67 was performed in 30 patients with benign prostatic hypertrophy (BPH), one with prostatic tuberculosis (TB), 22 with prostatic adenocarcinoma, one with prostatic transitional cell carcinoma and one with prostatic invasion from a bladder cancer. Specimens were aspirated from the prostate transrectally and a cytological smear were made. This antibody is specific for a proliferation-associated nuclear antigen. Alkaline phosphatase anti-alkaline phosphatase stained immunopositive nuclei red making positive or negative specimens easy to recognize. In BPH and TB smears, no immunopositive cell was reactive with Ki-67. In prostatic malignancy were found many immunopositive cells ranging from 2.5 to 10.2% (mean 5.9%) in prostatic adenocarcinoma (n = 22), and from 11.9 to 24.3% (mean 18.1%) in prostatic transitional cell carcinoma. Transitional cell carcinoma may have a much greater growth fraction than adenocarcinoma in prostatic tissue. Poorly differentiated adenocarcinoma showed a higher growth fraction (from 4.2 to 10.2%, mean 6.9%) than well differentiated (from 3.1 to 8.9%, mean 5.8%) and moderately differentiated adenocarcinoma (from 2.5 to 10.1%, mean 5.6%), but this difference was not significant. There was no correlation with age, clinical stage, bone metastasis or Böcking's cytological grade. In conclusion, immunohistochemical staining using Ki-67 on aspirated prostatic smear is visualizes the growth fraction of prostatic disease well and is useful to diagnose prostate cancer